Optimization of the strabismological examination of patients when planning surgical treatment of primary inferior oblique muscle overaction - V.B. Pushchina; I.L. Plisov; N.G. Antsiferova (Офтальмохирургия)
Purpose. To perform a comparative assessment of the results of strabismological examination of patients with primary inferior oblique muscle overaction according to the generally accepted and proposed methods. To analyze the change in the surgical procedure protocol depending on the results obtained. Material and methods. The research included 123 patients with a bilateral symmetric primary inferior oblique muscle overaction. The generally accepted method consisted in measuring the heterotropia magnitude when moving the gaze while turning the head left right and in measuring the magnitude of when moving the gaze following the ophthalmoscope beam when it is horizontally displaced upwards by 25° and downwards by 35° from 33 cm (assessment of V-pattern and its severity). The proposed method consisted in measuring the hypertropia magnitude of the adducted eye with the maximum fixing movement of the abducted eye gaze and in measuring the heterotropia magnitude with the maximum gaze movement upwards and downwards. Results. After the strabismological examination was carried out according to the proposed method, the average magnitude of hypertropia in adduction and V-pattern in the study group was statistically significantly (p<0.05) changed in the diagnostic protocols. A more prominent magnitude of hypertropia was revealed in 110 patients (89.43%). A more prominent V-pattern was diagnosed in 117 patients (95.12%). Studying the specifics of the oculomotor system disorders in patients resulted in optimization of the surgical procedure protocol in 83 patients according to the proposed method (67.48%). Conclusion. The average under-diagnosis of hypertropia and V-pattern during the examination according to the generally accepted method is 3.98±2.39° and 3.72±2°, respectively. Clarification of the oculomotor imbalance characteristics after the examination according to the proposed method requires a change in the surgical procedure protocol in more than 67% of cases.